मराठी

Prove the following trigonometric identities. sec A (1 − sin A) (sec A + tan A) = 1 - Mathematics

Advertisements
Advertisements

प्रश्न

Prove the following trigonometric identities.

sec A (1 − sin A) (sec A + tan A) = 1

बेरीज

उत्तर

We have to prove sec A(1 − sin A)(sec A + tan A) = 1

We know that sec2 A − tan2 A − 1 

So,

sec A(1 − sin A)(sec A + tan A) = {sec A(1 − sin A)}(sec A + tan A)

= (sec A − sec A sin A)(sec A + tan A)

= `(sec A - 1/cos A  sin A) (sec A + tan A)`     ...`(∵ sec theta = 1/costheta)`

= `(sec A - sin A/cos A) (sec A + tan A)`    ...`(∵ tan theta = sin theta/costheta)`

= (sec A − tan A)(sec A + tan A)

= sec2 A − tan2 A

= 1 = R.H.S.    ... (∵ sec2 θ = 1 tan2 θ)

shaalaa.com
  या प्रश्नात किंवा उत्तरात काही त्रुटी आहे का?
पाठ 11: Trigonometric Identities - Exercise 11.1 [पृष्ठ ४४]

APPEARS IN

आरडी शर्मा Mathematics [English] Class 10
पाठ 11 Trigonometric Identities
Exercise 11.1 | Q 18 | पृष्ठ ४४
सेलिना Mathematics [English] Class 10 ICSE
पाठ 21 Trigonometrical Identities
Exercise 21 (A) | Q 8 | पृष्ठ ३२४

संबंधित प्रश्‍न

`"If "\frac{\cos \alpha }{\cos \beta }=m\text{ and }\frac{\cos \alpha }{\sin \beta }=n " show that " (m^2 + n^2 ) cos^2 β = n^2`

 


Prove the following trigonometric identities.

`(1 + sin theta)/cos theta + cos theta/(1 + sin theta) = 2 sec theta`


Prove the following trigonometric identities.

`(1 + tan^2 A) + (1 + 1/tan^2 A) = 1/(sin^2 A - sin^4 A)`


Prove the following trigonometric identities.

`(cot A - cos A)/(cot A + cos A) = (cosec A - 1)/(cosec A + 1)`


Prove the following trigonometric identities.

`(1 + cos theta - sin^2 theta)/(sin theta (1 + cos theta)) = cot theta`


Prove the following identities:

`cotA/(1 - tanA) + tanA/(1 - cotA) = 1 + tanA + cotA`


Prove that:

cos A (1 + cot A) + sin A (1 + tan A) = sec A + cosec A


Prove that:

`sqrt(sec^2A + cosec^2A) = tanA + cotA`


`(sec^2 theta-1) cot ^2 theta=1`


`1/((1+ sintheta ))+1/((1- sin theta ))= 2 sec^2 theta`


`sqrt((1+sin theta)/(1-sin theta)) = (sec theta + tan theta)`


Prove that `( sintheta - 2 sin ^3 theta ) = ( 2 cos ^3 theta - cos theta) tan theta`


Write the value of `(1 - cos^2 theta ) cosec^2 theta`.


Write the value of ` sin^2 theta cos^2 theta (1+ tan^2 theta ) (1+ cot^2 theta).`


If sinθ = `11/61`, find the values of cosθ using trigonometric identity.


If sin2 θ cos2 θ (1 + tan2 θ) (1 + cot2 θ) = λ, then find the value of λ. 


\[\frac{\sin \theta}{1 + \cos \theta}\]is equal to 


Prove the following identity : 

`sqrt((1 + sinq)/(1 - sinq)) + sqrt((1- sinq)/(1 + sinq))` = 2secq


Prove that `(sin θ tan θ)/(1 - cos θ) = 1 + sec θ.`


Prove that : `1 - (cos^2 θ)/(1 + sin θ) = sin θ`.


Prove that `sin A/(sec A + tan A - 1) + cos A/(cosec A + cot A - 1) = 1`.


Prove the following identities.

`sqrt((1 + sin theta)/(1 - sin theta)` = sec θ + tan θ


If 1 – cos2θ = `1/4`, then θ = ?


Prove that `(tan(90 - theta) + cot(90 - theta))/("cosec"  theta)` = sec θ


If cos A = `(2sqrt("m"))/("m" + 1)`, then prove that cosec A = `("m" + 1)/("m" - 1)`


Prove that (1 – cos2A) . sec2B + tan2B(1 – sin2A) = sin2A + tan2B


If 4 tanβ = 3, then `(4sinbeta-3cosbeta)/(4sinbeta+3cosbeta)=` ______.


If sinA + sin2A = 1, then the value of the expression (cos2A + cos4A) is ______.


`sqrt((1 - cos^2theta) sec^2 theta) = tan theta` 


Prove that `(cot A - cos A)/(cot A + cos A) = (cos^2 A)/(1 + sin A)^2`


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×